Length-weight relationship and food and feeding habits of Otolithes cuvieri (Trewavas, 1974) from Mumbai - Telvekar, Prashanth A; Chakraborty, S K; Jaiswar, A K (Indian Journal of Fisheries, 2011)
The regression coefficients of length-weight relationship in females and males O. cuvieri revealed no significant difference and a common regression equation is presented as Log W = - 4.440 + 2.7977 Log L. Higher values of condition factorfound in certain months seems to be the preparation for the reproductive activities. The species is carnivorous, feeding mainly on fishes and crustaceans. About 50% of the identifiable food items constituted fishes like Harpodon nehereus, Cynoglossus arel and Coilia dussumieri indicating fish as the principal food item. Higher feeding intensity coincided with the advancement of thereproductive process and poor feeding with commencement of the spawningactivity.